MicroRNA miR-155-5p knockdown attenuates Angiostrongylus cantonensis-induced eosinophilic meningitis by downregulating MMP9 and TSLP proteins. Issue 1 (January 2021) - Zhou, Xumin; Zhang, Jinming; Liu, Jumei; Guo, Jianyu; Wei, Yong; Li, Jun; He, Peiqing; Lan, Tian; Peng, Lilan; Li, Hua
Graphical abstract: Highlights: MicroRNA miR-155-5p, a non-protein-coding and endogenous small RNA, is highly overexpressed in Angiostrongylus cantonensis infection. MiR-155-5p knockdown may attenuate A. cantonensis -induced eosinophilic meningitis (EM). MiR-155-5p targets SOCS1 and upregulates MMP9 and TSLP expression through activating STAT3 and NF-κB signal. A positive feedback loop is formed between miR-155-5p, STAT3, and NF-κB in A. cantonensis infection. Abstract: Angiostrongylus cantonensis infection is a major cause of eosinophilic meningitis (EM). Severe cases or cases that involve infants and children present poor prognoses. MicroRNAs (miRNAs), which are important regulators of gene expression in many biological processes, were recently found to be regulators of the host response to infection by parasites; however, their roles in brain inflammation caused by A. cantonensis are still unclear. The current study confirmed that miR-155-5p peaked at 21 days after A. cantonensis infection, and its expression was positively correlated with the concentration of excretory and secretory products (ESPs). We found that miR-155-5p knockdown lentivirus successfully ameliorated brain injury and downregulated the expression of major basic protein (MBP) in vivo, and the number of eosinophils in CSF (and the percentage of eosinophils in peripheral blood were also decreased in the miR-155-5p knockdown group. Moreover, the expression of several eosinophilic inflammation cytokines such as CCL6/C10, ICAM-1, and MMP9, declined after the miR-155-5p knockdown. SOCS1 protein, which is an important negative regulator of inflammation activation, was identified as a direct miR-155-5p target. We further detected the effect of miR-155-5p knockdown on phosphorylated-STAT3 and phosphorylated-p65 proteins, which were found to be negatively regulated by SOCS1 and play an important role in regulating the inflammatory response. We found that miR-155-5p knockdown decreased the activity of p-STAT3 and p-p65, thereby leading to lower expression of MMP9 and TSLP proteins, which were closely related to the chemotaxis and infiltration of eosinophils. Interestingly, the inhibition of p-STAT3 or p-p65 was found to induce the downregulation of miR-155-5p in an opposite manner. These observations suggest that a positive feedback loop was formed between miR-155-5p, STAT3, and NF-κB in A. cantonensis infection and that miR-155-5p inhibition might provide a novel strategy to attenuate eosinophilic meningitis.